Protocol for a scoping review on rehabilitation among individuals with traumatic brain injury who intersect with the criminal justice system. - Vincy Chan; Maria Jennifer Estrella; Zacharie Beaulieu-Dearman; Jessica Babineau; Angela Colantonio (PLoS ONE)
Traumatic brain injury (TBI), a leading cause of both death and disability worldwide, is highly prevalent among individuals who intersect with the criminal justice system. TBI is associated with increased behavioural, psychological, or negative outcomes, such as higher rates of mental health problems, aggression, and violent offending that may lead to negative interactions with the criminal justice system, reincarceration, and recidivism. Although rehabilitation is often recommended and holds promise in addressing TBI-related impairments, there is currently a paucity of reviews on rehabilitation for individuals with TBI who intersect with the criminal justice system (CJS). Concurrently, to the best of our knowledge, there is currently no review that considers rehabilitation among individuals with TBI who intersect with all parts of the CJS (i.e., policing, courts, corrections, and parole). This protocol is for a scoping review to address the above gaps, specifically, to identify the types of rehabilitation interventions and/or programs available to, or used by, individuals with TBI who intersect with all parts of the CJS. Primary research articles that meet pre-defined inclusion criteria will be identified from electronic databases (MEDLINE® ALL, Embase and Embase Classic, Cochrane CENTRAL Register of Clinical Trials, CINAHL, APA PsycINFO, Applied Social Sciences Index and Abstracts, Criminal Justice Abstracts, Nursing and Allied Health, and Dissertation and These Global), reference lists of included articles, and scoping or systematic reviews. Grey literature will also be searched to identify non-peer-reviewed reports. Retrieved articles will be screened by two reviewers and any disagreements will be resolved by a third reviewer. Data will be summarized quantitatively and analyzed using content analytic techniques. Intersecting identities will be charted and considered in the analysis. Stakeholders will be engaged to obtain feedback on preliminary results and the implications of findings. The scoping review will summarize the current state of rehabilitation available to, or used by, individuals with TBI who intersect with all parts of the CJS to (a) inform opportunities to integrate rehabilitation in the criminal justice system for diverse individuals and (b) identify opportunities for future research.